RNA Interference-Based Screen Reveals Concerted Functions of MEKK2 and CRCK3 in Plant Cell Death Regulation . Issue 1 (12th March 2020) - Yang, Yong; Liu, Jun; Yin, Chuanchun; de Souza Vespoli, Luciano; Ge, Dongdong; Huang, Yanyan; Feng, Baomin; Xu, Guangyuan; Manhães, Ana Marcia E. de A.; Dou, Shijuan; Criswell, Cameron; Shan, Libo; et al.
Abstract : A transient RNAi-based genetic screen helps elucidate the mechanisms of plant cell death control. Abstract: A wide variety of intrinsic and extrinsic cues lead to cell death with unclear mechanisms. The infertility of some death mutants often hurdles the classical suppressor screens for death regulators. We have developed a transient RNA interference (RNAi)-based screen using a virus-induced gene silencing approach to understand diverse cell death pathways in Arabidopsis ( Arabidopsis thaliana ). One death pathway is due to the depletion of a MAP kinase (MAPK) cascade, consisting of MAPK kinase kinase 1 (MEKK1), MKK1/2, and MPK4, which depends on a nucleotide-binding site Leu-rich repeat (NLR) protein SUMM2. Silencing of MEKK1 by virus-induced gene silencing resembles the mekk1 mutant with autoimmunity and defense activation. The RNAi-based screen toward Arabidopsis T-DNA insertion lines identified SUMM2, MEKK2, and Calmodulin-binding receptor-like cytoplasmic kinase 3 (CRCK3) to be vital regulators of RNAi MEKK1 -induced cell death, consistent with the reports of their requirement in the mekk1-mkk1/2-mpk4 death pathway. Similar with MEKK2, overexpression of CRCK3 caused dosage- and SUMM2-dependent cell death, and the transcripts of CRCK3 were up-regulated in mekk1, mkk1/2, and mpk4 . MEKK2-induced cell death depends on CRCK3. Interestingly, CRCK3-induced cell death also depends on MEKK2, consistent with the biochemical data that MEKK2 complexes with CRCK3. Furthermore, the kinase activity of CRCK3 is essential, whereas the kinase activity of MEKK2 is dispensable, for triggering cell death. Our studies suggest that MEKK2 and CRCK3 exert concerted functions in the control of NLR SUMM2 activation and MEKK2 may play a structural role, rather than function as a kinase, in regulating CRCK3 protein stability.